Not All Floating‐Harbor Syndrome Cases are Due to Mutations in Exon 34 of SRCAP. Issue 1 (16th October 2012) - Goff, Carine Le; Mahaut, Clémentine; Bottani, Armand; Doray, Berenice; Goldenberg, Alice; Moncla, Anne; Odent, Sylvie; Nitschke, Patrick; Munnich, Arnold; Faivre, Laurence; Cormier‐Daire, Valérie
ABSTRACT Floating‐Harbor syndrome (FHS) is a rare disorder characterized by short stature, delayed bone age, speech delay, and dysmorphic facial features. We report here the molecular analysis of nine cases, fulfilling the diagnostic criteria for FHS. Using exome sequencing, we identified SRCAP as the disease gene in two cases and subsequently found SRCAP truncating mutations in 6/9 cases. All mutations occurred de novo and were located in exon 34, in accordance with the recent report of Hood et al. However, the absence of SRCAP mutations in 3/9 cases supported genetic heterogeneity of FH syndrome. Importantly, no major clinical differences were observed supporting clinical homogeneity in this series of FHS patients.